2017
DOI: 10.3390/ijms18030560
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Brain Monoamines Underlie Behavioural Disruptions after Zebrafish Diet Exposure to Polycyclic Aromatic Hydrocarbons Environmental Mixtures

Abstract: Zebrafish were exposed through diet to two environmentally relevant polycyclic aromatic hydrocarbons (PAHs) mixtures of contrasted compositions, one of pyrolytic (PY) origin and one from light crude oil (LO). Monoamine concentrations were quantified in the brains of the fish after six month of exposure. A significant decrease in noradrenaline (NA) was observed in fish exposed to both mixtures, while a decrease in serotonin (5HT) and dopamine (DA) was observed only in LO-exposed fish. A decrease in metabolites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 54 publications
1
8
0
Order By: Relevance
“…We acknowledge that the results reported here using a freshwater species may not fully apply to marine fish, especially when considering the additional metabolic costs due to osmotic pressure maintenance in an hyperosmotic environment. There are however a large number of articles reporting similar toxicity pathways in marine and freshwater fish species for a number of biological functions such as growth (Bodiguel et al, 2009;Daouk et al, 2011), behavior (Gravato and Guilhermino, 2009;Oliveira et al, 2012;Vignet et al, 2017) and reproduction (Sun et al, 2015;Vignet et al, 2016). These studies therefore support the hypothesis that the present results on a freshwater fish species are indicative of what could happen in marine fish.…”
Section: Potential Consequences Of Life-history Effects Of Environmensupporting
confidence: 79%
“…We acknowledge that the results reported here using a freshwater species may not fully apply to marine fish, especially when considering the additional metabolic costs due to osmotic pressure maintenance in an hyperosmotic environment. There are however a large number of articles reporting similar toxicity pathways in marine and freshwater fish species for a number of biological functions such as growth (Bodiguel et al, 2009;Daouk et al, 2011), behavior (Gravato and Guilhermino, 2009;Oliveira et al, 2012;Vignet et al, 2017) and reproduction (Sun et al, 2015;Vignet et al, 2016). These studies therefore support the hypothesis that the present results on a freshwater fish species are indicative of what could happen in marine fish.…”
Section: Potential Consequences Of Life-history Effects Of Environmensupporting
confidence: 79%
“…In general, though, a neurotoxic effect in the present study cannot be excluded, since only one enzyme was investigated. It should be noted that recent studies focusing on the neuronal development in early life stages of fish indicated neurotoxic effects caused by petroleum hydrocarbons (Gao et al 2015 ; Vignet et al 2017 ; Xu et al 2017 ), indicating the relevance of neurotoxicity as a relevant endpoint for petroleum toxicity research. However, our current findings support previous conclusions that AChE is not a key biomarker for neurotoxic endpoints in petroleum research.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in psychological stress is a common trait observed relating to all examined pollutants [234]. In case of PAHs, a decrease in the neurotransmitter serotonin could be the driver for this behavioural change [235]. More recently, behavioural changes in the offspring of fish exposed to a mixture of PCBs and PBDEs showed that even if exposed parents displayed no change in behaviour, two offspring generations showed a significant increase in anxiety as adults while behaviour of larvae was modified in up to four offspring generations.…”
Section: Behavioural Screening Testsmentioning
confidence: 99%